2001
DOI: 10.1175/1520-0469(2001)058<3650:twtgaa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Weak Temperature Gradient Approximation and Balanced Tropical Moisture Waves*

Abstract: Horizontal temperature gradients are small in the tropical atmosphere, as a consequence of the smallness of the Coriolis parameter near the equator. This provides a strong constraint on both large-scale fluid dynamics and diabatic processes. This work is a step toward the construction of a balanced dynamical theory for the tropical circulation that is based on this constraint, and in which the diabatic processes are explicit and interactive. The authors first derive the basic fluid-dynamical scaling under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
588
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(665 citation statements)
references
References 56 publications
42
588
2
1
Order By: Relevance
“…This is referred to as the weak temperature gradient (WTG) approximation (Sobel et al 2001). In the case of slow rotations, the WTG approximation becomes valid globally, and the free-tropospheric temperatures are nearly constant at low pressure levels (only shown along the equator in Fig.…”
Section: Atmospheric Profile Over the Nightsidementioning
confidence: 99%
“…This is referred to as the weak temperature gradient (WTG) approximation (Sobel et al 2001). In the case of slow rotations, the WTG approximation becomes valid globally, and the free-tropospheric temperatures are nearly constant at low pressure levels (only shown along the equator in Fig.…”
Section: Atmospheric Profile Over the Nightsidementioning
confidence: 99%
“…Remarkably, the resulting patterns of precipitation and divergence were approximately the same as those that occurred in the full model. Bretherton dubbed this approximation the 'weak temperature gradient' (WTG) approximation (Sobel et al, 2001), and Sobel and Bretherton (2000) showed that it represents reasonably well the net effect of the rest of the model on any tropical grid column.…”
Section: Introductionmentioning
confidence: 99%
“…Related analyses using the present approach are work in progress. With (36), (37), we have a set of equations characterized by a single small parameter, ε. The limit ε → 0 is singular as is evident from the degeneration of the momentum equation (36) 1 in this limit.…”
Section: Distinguished Limit and Multiple Scales Ansatzmentioning
confidence: 99%
“…5, top left) develop on characteristic scales of 100 m to 10 km, both horizontally and vertically, and on time scales of up to 20 min. These are also the scales used in nondimensionalizing the governing equations in (36). Therefore, the special case of our solution ansatz in (38) with expansion functions…”
Section: Mesoscale Anelastic and Buoyancy-controlled Modelsmentioning
confidence: 99%
See 1 more Smart Citation